Impact of Project-Based Learning Implementation on Students Achievement in Green Chemistry Concepts - Febriani, Febriani; Hasan*, Muhammad; Khaldun, Ibnu; Khwaengmek, Wipavadee (Jurnal IPA & Pembelajaran IPA, 2025)
This study is grounded in the fact that students learning outcomes in green chemistry are relatively low, which are attributed to conventional teaching methods that involve students only minimally. This study aims to investigate the effect of project-based learning implementation on enhancing students learning outcomes in the topic of green chemistry. A quasi-experimental design with a pretestposttest control group was employed. The participants were tenth-grade students at MAS Darul Ihsan, assigned to an experimental class using PjBL and a control class applying traditional instruction. Data were collected through cognitive achievement tests and student activity observation sheets. The data were analyzed using an independent t-test, yielding a significance level of 0.000. Findings revealed a significant difference in learning outcomes between the two groups, with the experimental class achieving an N-Gain score of 0.73 (high category), while the control class obtained 0.37 (medium category). These results demonstrate that the implementation of PjBL effectively enhances student engagement and conceptual mastery and awareness of the importance of green chemistry principles. Therefore, PjBL can be recommended as an effective instructional model to optimize learning outcomes and foster environmentally conscious attitudes among students